Boreal predator co-occurrences reveal shared use of seismic lines in a working landscape - Tattersall, Erin R.; Burgar, Joanna M.; Fisher, Jason T.; Burton, A. Cole (Borealis, 2021)
AbstractInterspecific interactions are an integral aspect of ecosystem functioning that may be disrupted in an increasingly anthropocentric world. Industrial landscape change creates a novel playing field on which these interactions take place, and a key question for wildlife managers is whether and how species are able to coexist in such working landscapes. Using camera traps deployed in northern Alberta, we surveyed boreal predators to determine whether interspecific interactions affected occurrences of black bears (Ursus americanus), coyotes (Canis latrans), and lynx (Lynx canadensis) within a landscape disturbed by networks of seismic lines (corridors cut for seismic exploration of oil and gas reserves). We tested hypotheses of species interactions across one spatial-only and two spatiotemporal (daily and weekly) scales. Specifically, we hypothesized that 1) predators avoid competition with the apex predator, grey wolf (Canis lupus), 2) they avoid competition with each other as intraguild competitors, and 3) they overlap with their prey. All three predators overlapped with wolves on at least one scale, although models at the daily and weekly scale had substantial unexplained variance. None of the predators showed avoidance of intraguild competitors or overlap with prey. These results show patterns in predator space use that are consistent with both facilitative interactions or shared responses to unmeasured ecological cues. Our study provides insight into how industrial linear features affect the use of boreal landscapes by multiple predator species, and highlights that predator management may indirectly influence multiple species through interactions.